2014
DOI: 10.1556/aphysiol.101.2014.008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of l-carnosine on pro-antioxidant status in elite kayakers and canoeists

Abstract: Carnosine is a dipeptide formed from the amino acids β-alanine and histidine and found in large amounts in the brain and muscle, especially fast twitch muscle. Carnosine has an antioxidant role and accounts for about 10% of the muscle's ability to buffer the H+ ions produced by high intensity exercise. Due to the interesting role of carnosine, the aim of the study was observe the effects of carnosine intake on pro-antioxidant status in highly trained athletes exposed to intense exercise.Fourteen male athletes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…Carnosine (b-alanyl-L-histidine) is a dipeptide present in mammalian tissues and is available as an over-the-counter food additive. In humans, beneficial effects of carnosine have been shown in clinical trials in exercise physiology, psychology, psychiatry, and recently in heart failure (3)(4)(5)(6)(7)(8). Importantly, carnosine supplementation has not been associated with any significant side effects (3)(4)(5)7,8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carnosine (b-alanyl-L-histidine) is a dipeptide present in mammalian tissues and is available as an over-the-counter food additive. In humans, beneficial effects of carnosine have been shown in clinical trials in exercise physiology, psychology, psychiatry, and recently in heart failure (3)(4)(5)(6)(7)(8). Importantly, carnosine supplementation has not been associated with any significant side effects (3)(4)(5)7,8).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, beneficial effects of carnosine have been shown in clinical trials in exercise physiology, psychology, psychiatry, and recently in heart failure (3)(4)(5)(6)(7)(8). Importantly, carnosine supplementation has not been associated with any significant side effects (3)(4)(5)7,8). Ample animal evidence has suggested a role for carnosine supplementation in the prevention and treatment of type 2 diabetes and its complications as well as cardiovascular risk factors (dyslipidemia, hypertension) and disease (9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, both recreationally activity men [13] and women [12] who received BA supplementation had reduced LP after an acute bout of physical exercise (wen compared to pre-supplementation, but not to placebo condition). Although, in other studies with male athletes, carnosine [18] and BA [14] supplementation did not change/mitigate the increase in LP values after an acute bout of PE, despite increasing the GSH (Glutathione) antioxidant potential when compared to pre-treatment condition. Such studies from the same laboratory showed that improvement in antioxidant system seemed to occur only in women when compared to the presupplementation condition [12,13], instead other laboratories shown improvement in men [14,18].…”
Section: Introductionmentioning
confidence: 58%
“…Although, in other studies with male athletes, carnosine [18] and BA [14] supplementation did not change/mitigate the increase in LP values after an acute bout of PE, despite increasing the GSH (Glutathione) antioxidant potential when compared to pre-treatment condition. Such studies from the same laboratory showed that improvement in antioxidant system seemed to occur only in women when compared to the presupplementation condition [12,13], instead other laboratories shown improvement in men [14,18]. Therefore, it is necessary to systematize and meta-analyze studies with humans to evaluate the effectiveness of BA or carnosine supplementation as an antioxidant during PE-induced OS.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation